The Mobile Phone use of Senior High School Learners - Fernandez, Maricris R.; Dimla, Amirah O.; Ocampo, Leslie Jane F.; Cabrera, Tracy McGrady S.; Mamangun, Laura M.; Dela Cruz, Janice Angel C.; Dela Rosa, Rambel Joseph G.; Dominado, Noel L. (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
The information gathered from one of the secondary public schools in Cluster 1, Division of Pampanga's senior high schools for the academic year 2023–2024, the study looked at how the students used their phones. The study investigates the relationship between students' screen addiction and factors such as stress levels, physical activity levels, and lack of self-control. Through this discovery, an intervention plan is being developed by the researchers to effectively encourage senior high school students to balance their mobile phone usage. Approximately, 643 senior high learners from both levels participated in the study on the value of mobile phone usage among mobile phone users (MPUs).A mixed-method sequential explanatory design was used. According to the study, students who use screens excessively are more likely to experience stress, obsessive behavior, and a loss of self-control, among other negative consequences. On the contrary, physical activity is associated with lower stress levels among individuals. This study reveals senior high school students experience anxiety, eating problems, and smartphone addiction, impacting their behavior and mental health. Furthermore, the study found a correlation between stress levels and exercise and screen addiction. This connection may be the result of the study emphasizing the detrimental effects of excessive mobile phone use on the physical and emotional well-being of seniors in high school. Additionally, this study recommends managing digital resources, encouraging everyday life contacts, and encouraging a balanced approach to cell phone usage. Thus, the study highlights the significance of finding a balance between personal health and technology used to enhance student's educational experiences and quality of life. To enhance their academic performance and mental health, students should be taught about the dangers of excessive mobile phone usage, encouraged to practice personal wellness, and given preventative steps to follow.